FXR acts as a therapeutic target for ulcerative colitis via suppressing ferroptosis - Chenye Zhao; Xiaopeng Li; Mingchao Mu; Liyong Quan; Hang Yuan; Jianbao Zheng; Wei Zhao; Xuejun Sun; Junhui Yu (Molecular Medicine)
Abstract Background The involvement of ferroptosis in ulcerative colitis (UC) is increasingly acknowledged. Several investigations have revealed the various mechanisms by which the farnesoid X receptor (FXR) inhibits ferroptosis in certain diseases; however, its potential modulation of ferroptosis in UC remains unexplored. Methods The characteristics of FXR expression in colitis were evaluated in the GEO database, patient specimens, and mice with DSS-induced colitis. The role of FXR in ferroptosis was investigated by treating colitis mice with the intestine-restricted FXR agonist fexaramine (Fex) intragastrically. In vitro, Caco-2 cells challenged with RSL3 were used to study the role of FXR in modulating ferroptosis in intestinal epithelial cells (IECs). Results Fex significantly alleviated symptoms and impeded ferroptosis in mice with DSS-induced colitis. In vitro, Fex rescued Caco-2 cells from RSL3-induced ferroptosis. Mechanistically, FXR was capable of binding to the promoter region of SLC7A11 and upregulated the transcription of SLC7A11, which is beneficial for the synthesis of GSH. Knockdown of SLC7A11 partially abrogated the therapeutic effects of Fex, albeit incompletely. Further investigations revealed that FXR can also increase the protein stability of GPX4 by upregulating the deubiquitinase OTUB1. Conclusion This study highlights that FXR exerts therapeutic effects against colitis by antagonizing ferroptosis via transactivation of SLC7A11 and increasing GPX4 stability. These results suggest that FXR may be a therapeutic target for treating colitis by antagonizing ferroptosis. Graphical Abstract